Guides to the National Museum. Department of Oriental and Classical Antiquities. Oriental and Classical Antiquity: Egypt, Western Asia, Greece and Rome - Anonymus, A. (1950)
Mesopotamia: p. 27-32; fig. 7, 10 — Iran: p. 33-4 — Palestine, Syria: p. 35-7; fig. 8,9 — Asia Minor: p. 39-40 — Cyprus: p. 41-3; fig. 11-12 — Hama Collection: p. 74-81.